Calibration Method for Capacitive Silver Sensor Based on ATmega328 Microcontroller as a Membrane Potential Difference Measuring Instrument - Mahendra Putra, A. A. N. Surya; Rupiasih, Ni Nyoman; Supardi, I Wayan (BULETIN FISIKA; Vol 25 No 2 (2024): BULETIN FISIKADO - 10.24843/BF.2024.v25.i02.p11, 2024)
In making a measuring instrument, especially an electronics-based measuring instrument, it is necessary to calibrate the instrument made with a standard instrument while also knowing its measurement characteristics. In this study, a potential difference measuring instrument that was made using a silver capacitive sensor based on an ATmega328 microcontroller was calibrated using a standard reference electrode, namely Hanna HI 5414. The instrument was tested using a chitosan membrane and KCl solution. From the sensor calibration, an equation was found, namely Y = 0.9935 X + 0.0001 and has been converted to the ATmega328 microcontroller. The test results show that the accuracy of the measuring instrument reaches 99.82% with a measurement time of ± 3900 s faster than the standard instrument.